2019
DOI: 10.1136/bmjopen-2019-031420
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver index as a predictor of increased risk of cardiometabolic disease: finding from the Kuopio Ischaemic Heart Disease Risk Factor Study Cohort

Abstract: ObjectiveFatty liver disease (FLD), a global epidemic, is also a predictor of cardiometabolic disease (CMD) (type 2 diabetes or cardiovascular disease). Our objective was to examine whether progressive FLD, as assessed by fatty liver index (FLI), predicts increasing future CMD risk compared with relatively stable FLD, among middle-aged men.DesignProspective epidemiological study.SettingUniversity affiliated research centre in Kuopio, Eastern Finland.ParticipantsOur subjects were 501 men without CMD during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Another limitation of our study was the use of the FLI as a surrogate measure of NAFLD instead of histological assessment of NAFLD. Furthermore, because FLI comprises known CV risk factors (BMI, triglyceride levels, waist circumference) [28,32], these variables account for the associations observed in the current study. However, to overcome this limitation, we conducted analyses stratified by the presence or absence of these CV risk factors.…”
Section: Limitationsmentioning
confidence: 84%
“…Another limitation of our study was the use of the FLI as a surrogate measure of NAFLD instead of histological assessment of NAFLD. Furthermore, because FLI comprises known CV risk factors (BMI, triglyceride levels, waist circumference) [28,32], these variables account for the associations observed in the current study. However, to overcome this limitation, we conducted analyses stratified by the presence or absence of these CV risk factors.…”
Section: Limitationsmentioning
confidence: 84%
“…Several studies demonstrated that the FLI had excellent discriminative ability to detect ultrasonographic HS, and outperforms other non-invasive markers such as BMI, WC, TG, cholesterol and so on [ 18 20 ]. Furthermore, in addition to predicting HS, studies had shown that FLI was also associated with metabolic and cardiovascular disease, and all-cause mortality [ 21 23 ]. Therefore, FLI has great clinical application value in health screening and epidemiologic studies, particularly when ultrasound and other imaging examinations are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study was the use of the FLI as a surrogate measure of NAFLD instead of histological assessment of NAFLD. Furthermore, because FLI comprises known CV risk factors (BMI, triglyceride levels, waist circumference) [28,32], these variables account for the associations observed in the current study. However, to overcome this limitation, we conducted analyses stratified by the presence or absence of these CV risk factors.…”
Section: Limitationsmentioning
confidence: 98%